2021
DOI: 10.1371/journal.pone.0256723
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the visuo-proprioceptive illusion of movement and motor imagery of the wrist on EEG cortical excitability among healthy participants

Abstract: Introduction Motor Imagery (MI) is a powerful tool to stimulate sensorimotor brain areas and is currently used in motor rehabilitation after a stroke. The aim of our study was to evaluate whether an illusion of movement induced by visuo-proprioceptive immersion (VPI) including tendon vibration (TV) and Virtual moving hand (VR) combined with MI tasks could be more efficient than VPI alone or MI alone on cortical excitability assessed using Electroencephalography (EEG). Methods We recorded EEG signals in 20 he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Second, EEG modulations during finger stimulation are not hemispherically specific. According to [35, 36], mental imagery of finger movements, as well as tactile stimulation of the fingers, result in bilateral μ -ERD patterns whereas stimulation of more proximal parts of the arm cause predominantly contralateral ERD patterns [37, 38].…”
Section: Methodsmentioning
confidence: 99%
“…Second, EEG modulations during finger stimulation are not hemispherically specific. According to [35, 36], mental imagery of finger movements, as well as tactile stimulation of the fingers, result in bilateral μ -ERD patterns whereas stimulation of more proximal parts of the arm cause predominantly contralateral ERD patterns [37, 38].…”
Section: Methodsmentioning
confidence: 99%
“…Second, EEG modulations during finger stimulation are not hemispherically specific. According to (Vasilyev et al, 2016;Genna et al, 2017), mental imagery of finger movements, as well as tactile stimulation of the fingers, result in bilateral m-ERD patterns whereas stimulation of more proximal parts of the arm cause predominantly contralateral ERD patterns (Le Franc et al, 2021;Li et al, 2021). Third, we wanted to avoid any potential association of TS with motor movements which could have been the case for stimulation of the finger.…”
Section: Selection Of the Site For Tactile Stimulation And Imagerymentioning
confidence: 99%
“…This is in line with the studies that showed contralateral ERD in the mu & beta band in response to motor illusion vibrations (Yao et al, 2015; Schneider et al, 2021). Furthermore, providing motor illusion vibrations during MI allowed for stronger ERD than MI alone did (Le Franc et al, 2021). However, these authors noted that the ERD in response to passive vibrations was not different from the ERD during the MI with vibrations condition.…”
Section: Discussionmentioning
confidence: 99%